Contextual and corporate governance effects on carbon accounting and carbon performance in emerging economies. Issue 3 (5th March 2021) - Cordova, Carmen; Zorio-Grima, Ana; Merello, Paloma
Abstract : Purpose: This paper aims to explore the driving forces for having carbon reporting and carbon reduction management strategies in emerging and developing countries. Design/methodology/approach: The methodology employed uses logit and linear panel data models and generalized moments method, to avoid endogeneity problems. Findings: The results show that the carbon reporting decision is positively related to being located in Africa or America (as opposed to Asia), publishing a sustainability report and having certain corporate governance (CG) attributes such as a corporate social responsibility (CSR) committee, larger board size and an executive compensation policy based on environmental and social performance. Regarding the driving forces leading to a reduction of carbon emissions, no evidence is obtained on the effect of the variables considered. Practical implications: The evidence obtained is valuable, as it can help standard-setters in these geographical areas to promote actions in the field of CG to increase transparency. Nonetheless, additional measures to disclosure should be needed in the future to help decrease carbon emissions more effectively. Social implications: Raising awareness amongst companies helps mimetic isomorphism take place so that efforts can be made to report levels of pollution in an initial phase, which hopefully in the future may be managed to try to keep a decreasing path. Therefore, implications of this research are crucial for emerging and developing countries, as they are especially vulnerable to climate change. Originality/value: To the best of the authors' knowledge, this is the first paper to look into this phenomenon in emerging and developing countries from Asia, Africa and America. This contribution is unique as this research shows that location, publication of a sustainability report together with some CG attributes are drivers for carbon transparency.